2003
DOI: 10.1046/j.1365-2982.2003.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human swallowing behaviour by thermal and chemical stimulation in health and after brain injury

Abstract: Few data support thermal or chemical stimulation as therapy for neurogenic dysphagia. Our aims were to explore the behavioural effects of thermal (cold) and chemical (citrus) modalities on water swallowing in health (n = 65, mean age 45 years, 44 females) and acute stroke (n = 22, mean age 67 years, eight females). Multiple randomized timed 50-mL swallowing tests were performed for each of four water conditions: (a) room temperature (RT), (b) cold (CD), (c) citrus (CT) and (d) combined cold and citrus (CD + CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
0
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 35 publications
7
111
0
9
Order By: Relevance
“…Such studies showed changes in swallowing activity and a correlation with the findings of our study, as they also involved the taste and temperature receptors (13,19,22,27) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such studies showed changes in swallowing activity and a correlation with the findings of our study, as they also involved the taste and temperature receptors (13,19,22,27) .…”
Section: Discussionsupporting
confidence: 90%
“…Some stimuli, such as taste and temperature, have an influence on swallowing and also on bolus displacement times (5,13) . Kaatzke-McDonald et al (15) suggested the existence of thermo-receptive receptors at the pillars of fauces, which evoke swallowing when stimulated by a cold touch.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous use of sensory stimulation in the oral and pharyngeal cavities to augment patients' volitional control of swallowing [3,11], we compared sensory levels of electrical stimulation just above the participants' sensory threshold for detecting a tingling sensation on the skin, and found a significant improvement during swallowing on the NIH-SSS scale but no change on the PenAsp scale (Figure 3). The improvement on the NIH-SSS tended to be related to higher initial scores; that is the more severely affected patients were those who had the greatest improvement with stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…With the values of ingestion time and the number of swallows, we calculate: (1) interval between swallows -the total time of ingestion divided by the number of swallows; (2) ingestion flow -the total volume ingested (100 mL) divided by the time of ingestion; (3) swallowing volume -the total volume ingested (100 mL) divided by the number of swallows (1,9,13,14) . For statistical evaluation, a linear regression model was used with mixed effects (random and fixed effects).…”
Section: Methodsmentioning
confidence: 99%
“…The control of swallowing involves a complex interaction between muscles and nerves that coordinates the safe passage of swallowed material from the mouth to the stomach (13) . It is an ongoing process that involves the mouth, pharynx and esophagus, many oral structures, muscles and nerves.…”
Section: Introductionmentioning
confidence: 99%